The relationship between mathematical literacy and visual math literacy self-efficacy perceptions of middle school students - ŞENGÜL, SARE (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2019)
In this study, the levels of mathematical literacy and visual >math literacy self-efficacy perceptions of middle school students and the relationship between them were investigated. For this aim, the study was desgined as a correlational research model. The study group was determined according to convenience sampling. 328 middle school students (5th, 6th, 7th, and 8th graders) participated in this study with this sampling. In order to collect data, first, Mathematical Literacy Scale was developed. It was seen that the scale has just one dimension according to the exploratory factor analysis. It was found that the ratio chi(2)/df of the scale was found as 2.16 according to confirmatory factor analysis. This value showed that the scale indicates perfect fit. Besides, A Visual Math Literacy Self-Efficacy Perception Scale was used in order to measure the visual >math literacy self-efficacy perceptions of middle school students. As a result, it was determined that middle school students' mathematical literacy levels and their visual >math literacy self-efficacy perceptions' level are high. It was found that there is a high positive significant relationship between middle school students' mathematical literacy and their visual >math literacy self-efficacy perceptions.
Keywords: Mathematical literacy; Visual math literacy; Scale development; Middle school students; CONSTRUCT-VALIDITY